2010
DOI: 10.1177/0363546509359069
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of Anterior Bankart Repair Using Suture Anchors

Abstract: The findings may suggest that with cyclical loading up to 25 N there is no difference in gapping greater than 2mm, but a macrotraumatic event may demonstrate a difference in fixation during the initial postoperative period. Additional in vivo studies are needed to determine whether these differences affect the integrity of the repair construct and, ultimately, the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(124 citation statements)
references
References 40 publications
4
117
3
Order By: Relevance
“…Nho et al examined the differences in the biomechanics between repairs with simple stitch, suture anchor with horizontal mattress stitch, double-loaded suture anchor with simple stich, and knotless suture anchors [32]. This study found that all four constructs displayed less than 2-mm displacement when 25 N of cyclical load was applied; however, the knotless device exhibited significantly less force to ultimate failure while the other three constructs performed similarly [32]. While performance under cyclic loading is clinically important when considering daily tasks, ultimate load to failure may be important to consider when performing repair on contact athletes.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Nho et al examined the differences in the biomechanics between repairs with simple stitch, suture anchor with horizontal mattress stitch, double-loaded suture anchor with simple stich, and knotless suture anchors [32]. This study found that all four constructs displayed less than 2-mm displacement when 25 N of cyclical load was applied; however, the knotless device exhibited significantly less force to ultimate failure while the other three constructs performed similarly [32]. While performance under cyclic loading is clinically important when considering daily tasks, ultimate load to failure may be important to consider when performing repair on contact athletes.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…In most cases of anterior instability, an anteroinferior labral tear (Bankart lesion) is present, necessitating repair to the glenoid rim with any number of a variety of fixation devices. [8][9][10][11][12][13][14][15][16][17][18][19][20] The evolution of repair techniques for arthroscopic anterior shoulder…”
mentioning
confidence: 99%
“…In most cases of anterior instability, an anteroinferior labral tear (Bankart lesion) is present, necessitating repair to the glenoid rim with any number of a variety of fixation devices. [8][9][10][11][12][13][14][15][16][17][18][19][20] The evolution of repair techniques for arthroscopic anterior shoulder stabilization has essentially seen 3 "phases" over the past several decades, including transglenoid suture repair (Caspari technique), [21][22][23] repair with bioabsorbable tacks, and repair with suture anchors. For most patients, arthroscopic stabilization with suture anchors has become the accepted standard of care, 3,4,6,24-28 although as described, recurrence rates are still unacceptably high.…”
mentioning
confidence: 99%
“…Properties of suture anchors, including material, suture configuration, size, and technique are frequently updated. 22,23 The subjective and objective measures used to assess surgical outcome and success are very heterogeneous. Recurrence of instability falls along a wide spectrum, since apprehension in provocative positions to subluxations and dislocations.…”
Section: Discussionmentioning
confidence: 99%